The social selectivity of international mobility among German university students: A multi-level analysis of the impact of the Bologna process - Claudia Finger (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
This discussion paper deals with the social selectivity of internationally mobile German students prior to and after the Bologna Process thereby linking two mobility dimensions that a very rarely brought together - social and spatial mobility. Tackling this issue on multiple levels, I ask how student mobility is understood within key Bologna documents (declarations and communiqués) and how this is related to the social selectivity of international mobility among university students in Germany before and after the begin of the Bologna process (1998/99). At the European level, I examine the Bologna model of mobility as it is presented within central documents of the Bologna Process using a theory-guided qualitative content analysis. Sociological Neo-Institutionalism serves as theoretical and analytical framework to investigate institutional facilitators and barriers to the diffusion of the mobility model to the national and individual levels. Afterwards, I contextualize the German higher education system and describe the specific reception and translation of the Bologna model of mobility by German actors in higher education. At the individual level, Bourdieu's theory of educational reproduction is applied to the case of international student mobility to explain the socially stratified mobility behavior of German students with regard to the decision to go abroad, the country of destination and the duration of a study-related stay abroad. Further, I analyze the impact of the Bologna Process using survey data provided by the German National Association of Student Affairs (Deutsches Studentenwerk) of two cohorts: pre-Bologna (1997) and post-Bologna (2006). The main findings suggest that the social background of students is especially important when it comes to the decision to go abroad. However, if students have broken through the first obstacle and decided to go abroad, the influence of the social origin on the country of destination and the duration of mobile periods declines. The correlation between social origin and international mobility has, thus far, not weakened over the course of the Bologna Process. Rather, it has increased over time, indicating an incomplete diffusion in Germany of the relatively vague contents of the Bologna model of mobility from the European to the individual level. This result suggests that the Bologna process goals of enhanced spatial and social mobility have not (yet) been achieved. – – Dieses Discussion Paper behandelt die soziale Selektivität internationaler Mobilität deutscher Studierender im Bologna-Prozess und versucht, dabei zwei Mobilitätsdimensionen zu verbinden, die so bisher nur selten kombiniert wurden: räumliche und soziale Mobilität. Auf verschiedenen Ebenen wird untersucht, wie Studierendenmobilität in zentralen Bologna-Dokumenten (Erklärungen, Communiqués) verstanden wird und inwiefern dieses Verständnis mit der sozialen Selektivität internationaler Studierendenmobilität zusammenhängt. Auf der europäischen Ebene werden hierzu mithilfe einer theoriegeleiteten qualitativen Inhaltsanalyse zentrale Bologna-Dokumente untersucht und beschrieben. Der soziologische Neo-Institutionalismus dient dabei als theoretischer sowie analytischer Rahmen, mit dem eine mögliche Diffusion des Bologna-Mobilitätsmodells von der europäischen zur nationalen und individuellen Ebene erfasst werden soll. Anschließend werden das deutsche Hochschulsystem sowie die Aufnahme und Übertragung des Mobilitätsmodells durch zentrale deutsche Hochschulakteure dargestellt. Auf der letzten, der individuellen, Ebene wird schließlich Bourdieus Theorie der sozialen Reproduktion auf internationale Mobilität übertragen, um so die sozial stratifizierten Mobilitätsentscheidungen deutscher Studierender im Hinblick auf die Entscheidung, überhaupt ins Ausland zu gehen, auf das Zielland sowie auf die Dauer des studienbezogenen Auslandsaufenthalts zu erklären. Auf den vorangegangenen Kapiteln basierend werden außerdem Hypothesen zum Einfluss des Bologna-Prozesses gebildet, die im Anschluss mithilfe einer Pre-Bologna- (1997) und Post-Bologna-Kohorte (2006) der Sozialerhebung des Deutschen Studentenwerkes analysiert werden. Die Ergebnisse verweisen darauf, dass der soziale Hintergrund der Studierenden besonders für die Entscheidung, überhaupt ins Ausland zu gehen, großen Einfluss hat. Wenn die Studierenden diese erste Hürde genommen und sich für einen studienbezogenen Auslandsaufenthalt entschieden haben, verliert ihre soziale Herkunft allerdings an Bedeutung für die Wahl des Ziellands und die Dauer des Aufenthalts. Der Zusammenhang zwischen der sozialen Herkunft deutscher Studierender und ihrer Entscheidung, ins Ausland zu gehen, nahm im Laufe des Bologna-Prozesses nicht ab. Er stieg über die Zeit sogar an, was auf eine unvollständige Diffusion des ohnehin relativ vage formulierten Bologna-Mobilitätsmodells von der europäischen über die nationale zur individuellen Ebene hindeutet.
Keywords: 330